The Jihadi Current and the Lay Thinking: A "Re-Anchorage" Process Hypothesis - Dorra Ben Alaya (Peoples' Friendship University of Russia (RUDN University), 2021)
The Jihadi-salafist doctrine which is at the Islamist terrorism origin that affects several countries since the emergence of Al Qaeda in the late 80's, gave birth to the Islamic State of Iraq and Sham/Levant (ISIS/ISIL) established as a Caliphate in 2014. Despite the ISIS official military defeat in 2019, the Jihadi-Salafist current - whose history goes back a long way, is currently behind a number of attacks whether collective or individual, claimed by known organizations or committed in isolation. In our perspective, we try to apprehend the attraction power of the Jihadi narrative issue taking the Theory of Social Representations as a paradigmatic framework. This implies that we dont consider the Jihadi current membership as the manifestation of a deviation from normality or optimal rationality, but as the expression of a certain common sense resonance. More precisely, and taking the case of the Tunisian context, the success of the Jihadi narrative is explained by its effectiveness as an interpretive grid and as a guide for action, making it possible to re-anchor a reality lacking in meaning. This hypothesis of a re-anchoring implies that anchoring as described by Moscovici as one of the two processes at the origin of the social representations formation (with the objectification process), could be not only as a familiarization of the strange by inserting it in an already known pre-existing frame, but by substituting to the frame itself, a new one, in order to be able to insert familiar objects which would have lost their sense precisely because of the old frame itself. This hypothesis could offer a theoretical and heuristic perspective allowing the anchoring process to be conceived as a circular and non-definitive process.